1975
DOI: 10.1128/jvi.15.6.1308-1316.1975
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage SPO1-induced macromolecular synthesis in minicells of Bacillus subtilis

Abstract: SPOl bacteriophage injects its DNA into minicells produced by Bacillus subtilis CU403 divIVBl. The injected DNA is partially degraded to small trichloroacetic acid-precipitable material and trichloroacetic acid-soluble material. The injected DNA is not replicated; however, it serves as a template for RNA and protein synthesis. The RNA produced specifically hybridizes to SPOl DNA, and the amount of RNA hybridized can be reduced by competition with RNA isolated at all stages of the phage cycle from infected nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…We have therefore investigated the effect of PEN on the incorporation of amino acids by minicells of B. subtilis (Table 3). It was found that Lor D-alanine was incorporated into hot trichloroacetic acid-precipitable material to a much larger extent than the other amino acids tested (L-histidine, D,L-lysine, L-leucine, L-proline) and, indeed, as previously reported (29,30) we were unable to detect incorporation of L- a SP82-infected (multiplicity of infection -5) or uninfected minicells (0.5 ml; A6" = 0.5) were incubated in minimal medium with or without methionine at 37°C for 60 min.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We have therefore investigated the effect of PEN on the incorporation of amino acids by minicells of B. subtilis (Table 3). It was found that Lor D-alanine was incorporated into hot trichloroacetic acid-precipitable material to a much larger extent than the other amino acids tested (L-histidine, D,L-lysine, L-leucine, L-proline) and, indeed, as previously reported (29,30) we were unable to detect incorporation of L- a SP82-infected (multiplicity of infection -5) or uninfected minicells (0.5 ml; A6" = 0.5) were incubated in minimal medium with or without methionine at 37°C for 60 min.…”
Section: Resultssupporting
confidence: 84%
“…Protein synthesis induced in minicells is sensitive to CAM. It has been shown previously that protein synthesis occurs after phage infection of B. subtilis minicells (29). As a control for the effect of CAM and VAN on uninfected minicells, we checked the effect of CAM and VAN on phage-infected minicells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and SPP1 (22,50,58,63) express their entire genomes, T5, N4, SPOl, and SP82G (63, 68) do not proceed past the early stages of their development in infected minicells. Although repair of viral DNA (4) and synthesis of the replicative form of (X174 DNA (66) have been detected in infected minicells, replication of double-stranded phage DNAs has not been demonstrated (4,26,67,83,87).…”
mentioning
confidence: 99%